The Duality of Dharma and Adharma: A Comparative Analysis of Ram and Raavan in Tripathi’s Raavan: Enemy of Aryavarta and War of Lanka - Bhusal, Tilak; Bhattarai, Krishna Prasad (Journal of Research and Development, 2025)
This study explores the duality of dharma and adharma through a comparative analysis of Ram and Raavan’s moral frameworks in Amish Tripathi’s Raavan: Enemy of Aryavarta (2019) and War of Lanka (2022). Tripathi’s retelling of the Ramayana destabilizes traditional binaries of virtue and vice, portraying Raavan not merely as a villain but as a morally complex, tragic figure whose ethical reasoning often collides with, yet at times parallels, that of Ram. Drawing on Indian philosophical traditions, particularly the concepts of svadharma and rajadharma, alongside Western theoretical insights from Nietzsche’s critique of morality, Derrida’s deconstruction, Kant’s deontology, and Aristotle’s theory of tragic flaw, this article argues that Tripathi reimagines Raavan as an agent negotiating personal ambition, love, and political responsibility within a contested moral universe. The paper highlights how Raavan’s self-fashioned dharma reflects contextual and outcome oriented ethics, while Ram embodies principle-bound universal dharma. By situating this analysis within contemporary scholarship on mythological fiction, ethical criticism, and cultural semiotics, the article demonstrates that Tripathi’s novels engage readers in rethinking the fluidity, subjectivity, and interpretive nature of moral judgment in epic narratives. Ultimately, the study contends that dharma and adharma are not static absolutes but evolving constructs shaped by individual agency, social expectations, and cultural reinterpretations of myth.